La previsión social paternalista previa al control institucional: los empleados del Casino de Madrid, 1836-1910 - Zozaya-Montes, Maria (2013)
Here are studied the servants of a Gentlemanly Capitalism Club of the XIXth Century Spain, the "criados" of the Casino de Madrid, one of the most important institution cercles for the elites. Is tudied the profesional step between the personal relationships (1830-1880) and the administrative rules on this private profession.